Behavior of stud connections between concrete slabs and steel girders under transverse bending moment. (15th June 2016) - Lin, Zhaofei; Liu, Yuqing; Roeder, Charles W.
Highlights: An expression of tension–separation curves is proposed based on pull-out test results. Four stud connections between concrete slabs and steel girders are tested. Local behavior within the connection region is investigated numerically. Transverse stud arrangements in an actual steel–concrete composite bridge are provided. Abstract: The effect of transverse bending moment on stud connections is usually ignored in the design of steel–concrete composite bridges due to beam web flexibility. However, large transverse moment may arise near transverse stiffeners and diaphragms, because they constrain and stiffen the webs and cause tensile forces in stud connectors. Large web spacing and wide cantilevers increase these effects. This study experimentally and numerically investigates this behavior. Four groups of pull-out tests of a single stud connector under tension force are performed, and they provide insight into the behavior of stud connectors under direct tensile loading. Then four stud connections at interfaces near transverse stiffeners are tested to investigate their behavior under transverse bending moment. Numerical models of the stud connections are established to explore local behavior. The pull-out tests show that stud height greatly influences failure mode, tension strength and ultimate separation between the steel flange and the concrete slab. A tension–separation relationship is developed from the test results and used in subsequent numerical simulations. The stud connection tests suggest that longer studs can increase the bending moment and deformation capacities. Reduced longitudinal stud spacing significantly increases the stiffness, but may result in brittle failure of the concrete slab. Stud connectors should not be welded immediately over transverse stiffeners. Numerical simulations and test data compare well, and numerical results predict tensile forces in studs located near the steel web and in the region near stiffeners and other web restraint. The stud connectors in the two innermost rows on either side of a transverse stiffener provide the restraint to develop the tensile force in the studs caused by transverse bending moments. The force in a stud increases as its distance from the steel web increases and its distance from the transverse stiffener decreases. Shear–tension interaction should be checked for these connectors. Details of transverse stud arrangements with various stud heights are provided.